2021
DOI: 10.1186/s12871-021-01275-z
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational cohort pilot study of the association between midazolam use and delirium in elderly endoscopy patients

Abstract: Background Midazolam is a benzodiazepine commonly used in procedural sedation and general anaesthesia. Current anaesthetic guidelines advise the avoidance of benzodiazepines in elderly patients due to concerns of an increased risk of delirium. Delirium is associated with significant patient morbidity and mortality, while also increasing health costs. Despite this, midazolam is often used in elderly patients undergoing low risk procedures due to the benefits of rapid onset, anxiolysis and haemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Benzodiazepine was reported to be associated with abnormal mental symptoms in sedated patients, such as delirium 45 and paradoxical reactions 4,7 . For gastroscopy, delirium may have a lower risk (reported at <0.11%) for its short duration 37,46 . Paradoxical reactions occurred in 1.4–8.9% of patients undergoing endoscopy under midazolam sedation, 7–9 whereas no related data were available on remimazolam.…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepine was reported to be associated with abnormal mental symptoms in sedated patients, such as delirium 45 and paradoxical reactions 4,7 . For gastroscopy, delirium may have a lower risk (reported at <0.11%) for its short duration 37,46 . Paradoxical reactions occurred in 1.4–8.9% of patients undergoing endoscopy under midazolam sedation, 7–9 whereas no related data were available on remimazolam.…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam, a benzodiazepine with rapid onset, a short elimination half-life, small local irritation, a wide safety limit, a high therapeutic index, antianxiety effects, the ability to induce anterograde amnesia, and stable hemodynamics and without accumulation and residual effects, has been widely used for sedation, but its analgesic effect is unsatisfactory ( Lee et al, 2021 ). One study showed that compared with gastroscopy performed under anesthesia using only propofol and fentanyl, the amount of propofol decreased and the satisfaction of patients increased after the addition of midazolam ( das Neves et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it has been controversial whether antipsychotic treatment is effective for delirium. There was rare evidence to support the use of antipsychotics for agitation, and anesthesia guidelines recommend avoiding benzodiazepines in older patients [17,18]. However, in our report, a patient with POD was successfully cured with midazolam, and there was no postoperative cognitive decline in the patient at the 6month follow-up.…”
Section: Interventions and Follow-upmentioning
confidence: 52%